Efficacy and safety of care bundles in the treatment of delirium in ICU patients: a meta-analysis and systemic review - Dihui Fang; Lilan Zeng; Fang Kuang (BMC Nursing)
Abstract Objective The aim is to explore the impact of care bundles on the efficacy and safety of delirium management in intensive care unit (ICU) patients compared to standard care through a meta-analysis and systematic review. Method China National Knowledge Infrastructure (CNKI), Wanfang, PubMed, Web of Science (WOS), Embase, Cochrane, Chinese Biomedical Database (CBM), and VIP databases were searched from the database inception to December 1, 2024. The inclusion criteria based on the PICOS strategy include ICU patients (P), and randomized controlled trials (RCT) (S) comparing the treatment outcomes (such as incidence of delirium, duration of delirium, duration of mechanical ventilation, mortality rate, etc.) (O) between the care bundles (I) and standard care (C). Two investigators independently screened the literature, extracted the data, and assessed the quality of the included literature using the Cochrane Quality Assessment Tool. Meta-analysis was performed using STATA15.0 software. Results Eighteen studies were included with a total of 2,717patients involved. Most studies have a high/moderate risk of bias. The results of the meta-analysis demonstrated that care bundles was effective in decreasing the (1)incidence of delirium in ICU patients [risk ratio [RR] = 0.38, 95% confidence interval [CI] : 0.32, 0.45; P < 0.001], shortening the (2)duration of delirium(days) (weighted mean difference [WMD] = -1.60, 95% CI : -1.96, -1.23; P < 0.001), and (3)duration of mechanical ventilation in corresponding patients(days) (standardized mean difference [SMD] = -1.65, 95% CI : -2.40, -0.89; P < 0.001). However, there was no statistical difference in patient (4) mortality (RR = 0.78, 95% CI : 0.44, 1.40; P = 0.41). Conclusions Care bundles have positive effects on delirium in ICU patients. However, results with significant heterogeneity should be interpreted with caution, and differences in bundles need to be taken into account. More multi-center, largesample randomized controlled studies are required to further explore the optimal components and combinations of care bundles.